Effect of Phosphorus on the leaf yield, nutrient uptake and P-use efficiencies of sun cured chewing tobacco (Nicotiana tobacum) grown in Tamil Nadu - KUMARESAN, M; SWAMY, A V S R; KRISHNAMURTHY, V; KUMAR, P HARISHU; RAO, C C S; ATHINARAYANAN, R (The Indian Journal of Agricultural Sciences, 2014)
A field experiment was conducted during 2005-2009 to study the effect of various P management practices on the productivity, chewing quality, nutrient uptake, P-use efficiencies on chewing tobacco. There is a dire need to reduce the P requirement for chewing tobacco (Nicotiana tabacum L.), as it is costlier and scarce. First grade leaf yield (FGLY) and total cured leaf yield (TCLY) with 50,75 and 100% recommended P with or without phospho bacteria (PSB) are comparable. The FGLY and TCLY increase varied between 7 to 20 % and 19 to 30 % respectively over no P. Phosphorus application irrespective of the levels improved the chewability (Score >60) over no P. The uptake of NPK and soil available P improved with levels of P with or without PSB over no P. Phosphorus application every year improved the soil available P. The P balance showed loss of P in all the treatments. P-use efficiency (39.5- 42.3 kg/kg), P-uptake efficiency (0.12 - 0.15 kg/kg) , agronomic efficiency (0.12 - 0.15 kg/kg) , recovery efficiency (7.27 7.55%) and partial factor productivity (138 - 148 kg/kg) was higher at 50% P with or without PSB. Physiological efficiency was higher at 100% P +PSB (315 kg/ha) in the first year and 50% P (395.3 kg/ha) in the second year. Net returns and B:C ratio with 100% P was comparable with 75 and 50 % P with or without PSB. It was concluded that 50% recommended P (22 kg P/ha) would be sufficient for higher yield , net returns, better leaf chemistry and P-use efficiency.